Modulation of Auditory Cortex Response to Pitch Variation Following Training with Microtonal Melodies - Zatorre, Robert J.; Delhommeau, Karine; Zarate, Jean M. (Frontiers in Psychology, 2012)
We tested changes in cortical functional response to auditory configural learning by training ten human listeners to discriminate micromelodies (consisting of smaller pitch intervals than normally used in Western music). We measured covariation in blood oxygenation signal to increasing pitch-interval size in order to dissociate global changes in activity from those specifically associated with the stimulus feature of interest. A psychophysical staircase procedure with feedback was used for training over a two-week period. Behavioral tests of discrimination ability performed before and after training showed significant learning on the trained stimuli, and generalization to other frequencies and tasks; no learning occurred in an untrained control group. Before training the functional MRI data showed the expected systematic increase in activity in auditory cortices as a function of increasing micromelody pitch-interval size. This function became shallower after training, with the maximal change observed in the right posterior auditory cortex. Global decreases in activity in auditory regions, along with global increases in frontal cortices also occurred after training. Individual variation in learning rate was related to the hemodynamic slope to pitch-interval size, such that those who had a higher sensitivity to pitch-interval variation prior to learning achieved the fastest learning. We conclude that configural auditory learning entails modulation in the response of auditory cortex specifically to the trained stimulus feature. Reduction in blood oxygenation response to increasing pitch-interval size suggests that fewer computational resources, and hence lower neural recruitment, is associated with learning, in accord with models of auditory cortex function, and with data from other modalities.